👤

Multiply the following:
1. (4x - 5)(3x + 6) =
2. (7x2 + 9x -12)(2x - 5) =​


Sagot :

Answer:

Multiply the following:

1. (4x - 5)(3x + 6) =-120

2. (7x2 + 9x -12)(2x - 5) =1220

yan po

Answer:

1) [tex]12x^2+9x-30[/tex]

2) [tex]14x^3-17x^2-69x+60[/tex]

Step-by-step explanation:

1) [tex](4x-5)(3x+6)[/tex]

[tex]=(4x+-5)(3x+6)[/tex]

[tex]=(4x)(3x)+(4x)(6)+(-5)(3x)+(-5)(6)[/tex]

[tex]=12x^2+24x-15x-30[/tex]

[tex]=12x^2+9x-30[/tex]

2)[tex](7x^2+9x-12)(2x-5)[/tex]

[tex]=(7x^2+9x+-12)(2x+-5)[/tex]

[tex]=(7x^2)(2x)+(7x^2)(-5)+(9x)(2x)+(9x)(-5)+(-12)(2x)+(-12)(-5)[/tex]

[tex]=14x^3-35x^2+18x^2-45x-24x+60[/tex]

[tex]=14x^3-17x^2-69x+60[/tex]